2015
DOI: 10.1097/jps.0000000000000060
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preoperative Training and Therapeutic Play on Children’s Anxiety, Fear, and Pain

Abstract: The aim of the study is to determine the effectiveness of education and therapeutic play applied in the preoperational period to decrease the anxiety, fear, and pain levels of children in the postoperative period.Methods: This study is a quasi-experimental and cross-sectional research. Three hundred children aged 7-12 years and suitable for the research criteria, referred to two pediatric hospitals in the northern region of Turkey for surgery, are the sample of the study. Each group (control group, training gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…Other studies show that therapeutic games decreased anxiety in children who experienced the game session in the hospital environment. After the play sessions, children feel safer because they learn the environment and the procedures [26,27,30,33,34]. In some sessions, nurse techniques are simulated in the toys, which allowed the child to move from a passive to an active role, reducing the fear of these procedures [27,29] and establishing a positive child-nurse relationship [26,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies show that therapeutic games decreased anxiety in children who experienced the game session in the hospital environment. After the play sessions, children feel safer because they learn the environment and the procedures [26,27,30,33,34]. In some sessions, nurse techniques are simulated in the toys, which allowed the child to move from a passive to an active role, reducing the fear of these procedures [27,29] and establishing a positive child-nurse relationship [26,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…19 To prepare the children for surgical intervention, an educational video about the operating room and other interventions was shown, and the fear score before and after the surgical intervention decreased significantly. 20 Fear scores were also less determined in children who were shown a video that provided information about informative and interactive surgical intervention. 21 In this research, the fear of children in the puppet group before surgery was found to be lower in the second and third measurements compared to the animation group.…”
Section: Discussionmentioning
confidence: 98%
“…Hastanede yatmanın çocuk üzerinde oluşturduğu majör stresörler arasında aileden ayrılma da yer almaktadır (1,2 (22). Bir başka çalışmada kullanılan terapötik oyunun çocuklarda oluşan anksiyete, korku ve ağrı düzeyini azaltmada etkili olduğu belirlenmiştir (23). Diğer bir çalışmada çocukların hastanede park, oyun odası, sinema odası, bilgisayar ve ilköğretim odası istedikleri yer almaktadır (10).…”
Section: Discussionunclassified